1997
DOI: 10.1080/08927019709378325
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rock‐type on the settlement ofbalanus balanoides(L.) cyprids

Abstract: The nature of surfaces has been shown to have significant effects on the settlement of marine organisms. However, the few studies on the effect of natural rock surfaces on barnacle settlement have produced conflicting results. Here the settlement of Balanus balanoides (L.) cyprids on a variety of natural rock-types is investigated in situ in the absence of strong colour cues. The potential effect of surface texture was minimised as only 5 of the 15 examined rocks showed significant differences in surface rugos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Physical cues known to influence cypris larvae involve salinity (Dineen & Hines 1994a,b), temperature (O'Connor & Richardson 1994, Kitamura & Nakashima 1996, light (Crisp & Barnes 1954, Raimondi 1990), wave strength (Raimondi 1990), benthic boundary layer flows (Crisp 1955, Wethey 1986, Mullineaux & Butman 1991, Mullineaux & Garland 1993, Judge & Craig 1997 and the characteristics of the surface: physico-chemistry (Raimondi 1988b, Holmes et al 1997), surface energy (Rittschof Costlow 1989a;b, Roberts et al 1991, Maki et al 1992, Becker 1993, O'Connor & Richardson 1994, Becker et al 1997, Holmes et al 1997, vibration , Rittschof et al 1998, texture (Crisp & Barnes 1954, Letourneux & Bourget 1988, Raimondi 1990, Hills & Thomason 1996, 1998a and small-scale heterogeneity (Bergeron & Bourget 1986, Chabot & Bourget 1988, Walters 1992, Lernire & Bourget 1996, Miron et al 1996, Walters & Wethey 1996.…”
Section: Tidal Heightmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical cues known to influence cypris larvae involve salinity (Dineen & Hines 1994a,b), temperature (O'Connor & Richardson 1994, Kitamura & Nakashima 1996, light (Crisp & Barnes 1954, Raimondi 1990), wave strength (Raimondi 1990), benthic boundary layer flows (Crisp 1955, Wethey 1986, Mullineaux & Butman 1991, Mullineaux & Garland 1993, Judge & Craig 1997 and the characteristics of the surface: physico-chemistry (Raimondi 1988b, Holmes et al 1997), surface energy (Rittschof Costlow 1989a;b, Roberts et al 1991, Maki et al 1992, Becker 1993, O'Connor & Richardson 1994, Becker et al 1997, Holmes et al 1997, vibration , Rittschof et al 1998, texture (Crisp & Barnes 1954, Letourneux & Bourget 1988, Raimondi 1990, Hills & Thomason 1996, 1998a and small-scale heterogeneity (Bergeron & Bourget 1986, Chabot & Bourget 1988, Walters 1992, Lernire & Bourget 1996, Miron et al 1996, Walters & Wethey 1996.…”
Section: Tidal Heightmentioning
confidence: 99%
“…Habitat selection is influenced by boundary layer structure (Crisp 1955, Wethey 1986, Mullineaux & Butman 1991, Mullineaux & Garland 1993, Judge & Craig 1997, the nature of the surface (physico-chemistry: Raimondi 1988b, Holmes et al 1997surface energy: Rittschof & Costlow 1989a,b, Roberts et al 1991, Maki et al 1992, Becker 1993, O'Connor & Richardson 1994, Becker et al 1997, Holmes et al 1997vibrations: Branscomb & Rittschof 1984, Rittschof et al 1998texture: Crisp & Barnes 1954, Letourneux & Bourget 1988, Raimondi 1990, Hills & Thomason 1996, 1998a; and small-scale heterogeneity: Bergeron,& Bourget 1986, Chabot & Bourget 1988, Walters 1992, Gregoire & Bourget 1996, Lemire & Bourget 1996, Miron et al 1996, Walters & Wethey 1996, substratum biological cues (associated with the presence of natural biofilms: Hudon & Bourget 1981, Letourneux & Bourget 1988& Todd 1-998; conspecific adults: Knight-Jones--1-953, Rittschof et al 1984, &ttschof 1985, Gabbott & Larman 1987, Letourneux & Bourget 1988, Chabot & Bourget 1988, Raimondi 1988a…”
Section: Introductionmentioning
confidence: 99%
“…In these South Australian boulder reefs, assemblages of mobile species under boulders were unique according to the rock type of the reef (although this was only true underneath and not on top of boulders), which has similarly been found in other marine habitats (Raimondi 1988, Holmes et al 1997, Bavestrello et al 2000, Schiaparelli et al 2003, Herbert & Hawkins 2006. The differing rock type amongst reefs is only one possible mechanism that may be responsible for this, as other environmental features that vary among reefs of different rock type may be associated with the biotic variables.…”
Section: Q1: Do Assemblages On Siltstone and Limestone Reefs Differ?mentioning
confidence: 95%
“…However, evidence for an effect of rock type on benthic species is sparse. Some studies have found associations between biotic structure and rock type at scales encompassing different geographical locations (Vermeij 1971, Raimondi 1988, Davidson & Chadderton 1994, Holmes et al 1997, Bavestrello et al 2000, Guidetti & Cattaneo-Vietti 2002, Schiaparelli et al 2003, Guidetti et al 2004, Herbert & Hawkins 2006, Green et al 2012). The associations found at this scale, however, have rarely been confirmed at the boulder scale (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation